From natural threat to disaster: A historical construction of the earthquake and tsunami of 1960 in Saavedra - Inostroza-Matus, Cristian Ceferino (2020)
Disasters constitute complex phenomena that are the result of socioenvironmental and territorial processes that reconfigure nature and society. Despite the undeniable role of nature in the construction and production of disasters, these disasters are conditioned by historical processes of accumulation that make certain populations vulnerable. The ethnic and racial component of this vulnerability plays a central role in determining who will be more affected. The disaster of 1960 in the commune of Saavedra (Chile) is an empirical example of this. Here the impacts and destruction caused by the strongest earthquake registered in history and subsequent tsunami are not only marked by the magnitude of this phenomenon but are the result of a process of historical construction of the territory. This article analyzes this disaster from a historical and critical geography perspective that seeks to expose how the territory and its population are transformed, generating the necessary conditions for a disaster to take place. Through the revision of texts of explorers, military reports, maps, autobiographies, scientific research projects, site visits, and the support of system of geographic information, this article seeks to reconstruct the process of the conformation of territory in Saavedra, highlighting the direct relationship that exists between the invasion of the Mapuche territory Lafkenche by the Chilean State and the worst disaster in its history more than a decade later.